Single-component photovoltaic adhesive with low water vapor transmittance and high curing speed and preparation method of single-component photovoltaic adhesive
By developing a single-component silicone sealant with a specific ratio and process treatment, the problem of insufficient water vapor transmission and humidity resistance when existing photovoltaic modules face new photovoltaic products such as offshore and heterojunction is solved, and the effect of low water vapor transmission and fast curing speed is achieved, reducing production costs, and excellent aging resistance.
Patent Information
- Application Number
- CN202411728100.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-28
- Publication Date
- 2025-03-14
AI Technical Summary
When existing photovoltaic modules face new photovoltaic products such as offshore and heterojunction, the water vapor transmission rate and humidity resistance are insufficient, resulting in leakage damage and other problems. At the same time, the use of conventional sealants and butyl tape increases production costs.
Develop a single-component silicone sealant to achieve the effect of low water vapor transmission and fast curing speed through specific ratios and process treatments, and is directly used in water vapor-sensitive components such as offshore photovoltaics and heterojunctions.
It achieves several times lower water vapor transmission than conventional photovoltaic sealants, while maintaining faster curing speed, reducing component production costs, and having excellent aging resistance.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photovoltaic adhesives, and in particular relates to a single-component photovoltaic adhesive with low water vapor permeability and fast curing speed and a preparation method thereof. Background Art
[0002] Photovoltaic technology has been developing rapidly in my country in the past two decades. By 2023, my country will use 470 million kilowatts of photovoltaic power generation, which plays an important role in the development of new energy. And with the current trend of increasing natural resources, the scale of photovoltaic power generation will become larger and larger. However, photovoltaic components are now in a serious state of involution and are updated more quickly. New photovoltaic products such as offshore photovoltaics, heterojunctions, and perovskites are constantly being mentioned. Usually photovoltaic components need to experience severe natural weather, such as rain, snow, typhoons, sandstorms, etc. Therefore, in order to prevent water vapor from entering the components, hydrolyzing the cells and causing leakage damage, silicone sealants are needed for encapsulation and water-blocking treatment. However, new photovoltaic products such as offshore photovoltaics and heterojunctions are more sensitive to water vapor, so the requirements for the water-blocking type of encapsulation and sealing products are particularly high.
[0003] Chinese patent CN17659907A introduces a butyl tape made of butyl rubber, polyisobutylene and alumina as basic raw materials. The advantages of this butyl tape are low water vapor transmission rate and good UV resistance. However, there are still problems such as resistance to moisture and heat, high and low temperature resistance, etc. In addition, butyl rubber needs to be used in combination with silicone sealant, which will increase the production cost of components.
[0004] Chinese patent CN117683488A also introduces a hot melt butyl adhesive, the main advantage of which is that the water vapor transmission rate is relatively low, but the resistance to moisture and heat and UV resistance are not solved. And it also needs to be encapsulated with silicone sealant, and then blocked with butyl adhesive. Summary of the invention
[0005] In order to overcome the above technical defects, the purpose of the present invention is to provide a single-component silicone sealant with low water vapor transmission rate, fast curing speed and good aging resistance, which can be directly used in offshore photovoltaics or new photovoltaic modules that are sensitive to water vapor, such as heterojunctions. It avoids the need to use a layer of butyl glue to prevent water vapor transmission while using conventional sealants, which can not only reduce the production process of modules, but also reduce the production cost of modules.
[0006] The present invention provides a single-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed, comprising the following raw materials in parts by weight: 50-150 parts of α,ω-dihydroxy polydimethylsiloxane; Butyl rubber 5-20 parts; Polyisobutylene 2-10 parts; 100-200 parts of modified nano calcium carbonate; 1-10 parts of cross-linking agent; 0.5-5 parts of coupling agent; Catalyst 0.01-0.1 parts.
[0007] More preferably, the following raw materials are included in parts by weight: 100-150 parts of α,ω-dihydroxy polydimethylsiloxane; Butyl rubber 10-20 parts; Polyisobutylene 5-10 parts; 150-200 parts of modified nano calcium carbonate; 5-10 parts of cross-linking agent; Coupling agent 0.5-2 parts; Catalyst 0.01-0.05 parts.
[0008] The structural formula of the α,ω-dihydroxy polydimethylsiloxane is HO-[(CH3)2SiO] m -H, wherein m is 50-1000; the kinematic viscosity of α,ω-dihydroxy polydimethylsiloxane at 25°C is preferably 10000-80000cp, further preferably 20000-80000cp, and more preferably 20000cp; The butyl rubber has a kinematic viscosity of 5000-800000 cp at 25° C., preferably 50000-800000 cp, and more preferably 100000 cp-500000 cp; The polyisobutylene has a kinematic viscosity at 25° C. of 100,000 to 800,000 cp, preferably 200,000 to 800,000 cp, and more preferably 500,000 to 800,000 cp.
[0009] The modified nano calcium carbonate is prepared from calcium carbonate emulsion and modified with stearic acid; the water content of the modified nano calcium carbonate is 0.1-0.5% and the specific surface area is 15-40m 2 / g, oil absorption value is 25~35m 2 / g, whiteness of 93-97, particle size and shape of prism or cube; preferably, moisture content of 0.1-0.3%, specific surface area of 25-40m 2 / g, oil absorption value is 30-35m 2 / g, whiteness is 93-97, and particle size is prismatic.
[0010] The coupling agent is one or more of a monoaminosilane coupling agent, a bisaminosilane coupling agent, an epoxysiloxane or an oligomer amino coupling agent; preferably, the coupling agent is a monoaminosilane coupling agent and a bisaminosilane coupling agent compounded in a mass ratio of 3:1.
[0011] The crosslinking agent is one or more of phenyltributylon oxime siloxane, tetrabutyl oxime siloxane, methyltributylon oxime siloxane or vinyltributylon oxime siloxane, preferably at least one of phenyltributylon oxime siloxane or tetrabutyl oxime siloxane.
[0012] The catalyst is at least one of dibutyltin diacetate, dibutyltin dilaurate, chelated tin, stannous octoate or stannous isooctanoate.
[0013] A method for preparing a single-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed comprises the following steps: (1) heating and kneading α,ω-dihydroxypolydimethylsiloxane, butyl rubber and polyisobutylene; (2) Add modified nano calcium carbonate, heat and knead; (3) After cooling, add the cross-linking agent and catalyst and stir; (4) Add a coupling agent and stir to obtain a single-component, low water permeability, fast-curing sealant.
[0014] The kneading temperature in step (1) is 100-160°C, preferably 120-150°C, and more preferably 140-150°C; the kneading time in step (1) is 10-60 min, preferably 15-45 min, and more preferably 25-35 min; the kneading temperature in step (2) is 90-140°C, preferably 110-140°C, and more preferably 130-140°C; the kneading time in step (2) is 2-8 h, preferably 2-5 h, and more preferably 3~4h; after step (3) is cooled to 40~50°C, a cross-linking agent and a catalyst are added; the stirring temperature of step (3) and step (4) is 30~80°C, preferably 30~60°C, and more preferably 40~50°C; the stirring time of step (3) is 10~60min, preferably 20~50min, and more preferably 25~35min; the stirring time of step (4) is 10~60min, preferably 25~45min, and more preferably 30~40min.
[0015] A single-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed, used as a sealant for offshore photovoltaic or heterojunction photovoltaic products.
[0016] The present invention provides a low water permeability, fast-curing single-component photovoltaic sealant, which has a lower water vapor permeability than conventional photovoltaic sealants, can be used on offshore photovoltaic components that are more sensitive to water vapor, and can be used on heterojunction components. The process of using butyl tape to reduce water resistance can be eliminated, thereby reducing component costs and achieving the same use effect.
[0017] Generally speaking, the lower the water vapor permeability of a single-component sealant, the slower the curing speed. This patent firstly improves the curing speed by improving the process so that the silicone is prepolymerized at the beginning; secondly, it uses tetrabutyl ketone oxime siloxane and phenyl tributyl ketone oxime siloxane with faster curing speed to improve the curing speed. While achieving low water permeability, the curing speed of the single-component sealant of the present invention can even be faster than that of ordinary single-component sealants.
[0018] Specifically, compared with the prior art, the present invention has the following advantages: 1. The low water permeability, fast curing single-component sealant prepared by the present invention has a water vapor permeability several times lower than that of the photovoltaic sealants commonly used on the market, and the curing speed is not reduced, and can be used in the offshore photovoltaic field which is more sensitive to water vapor.
[0019] 2. Heterojunction and perovskite have particularly low requirements for water vapor permeability, so in conventional applications, after packaging with ordinary sealant, a layer of butyl glue is also used to reduce water resistance; the low water permeability and fast-curing sealant provided by the present invention can directly omit the process of using butyl glue, and achieve low water permeability during packaging, thereby greatly reducing the cost of the component.
[0020] 3. The low water permeability, fast curing single-component sealant prepared by the present invention has excellent aging resistance and can well replace the existing commonly used sealants without obvious hidden dangers. DETAILED DESCRIPTION
[0021] The embodiments of the present invention will be described in detail below with reference to examples. The following examples are only used to illustrate the present invention and should not be construed as limiting the scope of the present invention.
[0022] Example 1 The proportions of the raw materials are as follows: 120 parts of α,ω-dihydroxy polydimethylsiloxane; Butyl rubber 18 parts; 5 parts of polyisobutylene; 180 parts of modified nano calcium carbonate; 5 parts of cross-linking agent; 2 parts of coupling agent; 0.05 parts of catalyst.
[0023] Among them, the kinematic viscosity of α,ω-dihydroxy polydimethylsiloxane at 25°C is 20000cp; The kinematic viscosity of butyl rubber at 25°C is 500,000 cp; The kinematic viscosity of polyisobutylene at 25°C is 800,000 cp.
[0024] The water content of modified nano calcium carbonate is 0.3% and the specific surface area is 40m 2 / g, oil absorption value is 35m 2 / g, whiteness is 97, and particle size shape is prismatic.
[0025] Preparation method of modified nano calcium carbonate: Limestone is calcined to obtain CaO and CO2, CaO is digested with water to generate Ca(OH)2 emulsion, and then carbonization reaction is carried out with CO2 gas, and appropriate crystal form control agent is added to control the crystal form. When the carbonization is completed, the desired calcium carbonate slurry is obtained, and then dehydration, drying and surface treatment are carried out to obtain calcium carbonate; calcium carbonate is mixed and stirred with stearic acid to obtain stearic acid-modified nano calcium carbonate.
[0026] Preparation steps: (1) The α,ω-dihydroxypolydimethylsiloxane, butyl rubber and polyisobutylene are heated and evacuated in a kneader until the vacuum degree reaches 0.05 MPa and the temperature reaches 145°C, and then stirred for 30 minutes; (2) After the temperature of the glue drops to 130°C, add the modified nano-calcium carbonate into the kneader and stir evenly, then evacuate the mixture to a vacuum degree of 0.05 MPa, heat it to 135°C and stir for 4 hours; (3) Cool down to 50°C, mix the crosslinking agent (tetrabutyl ketone oxime siloxane) and the catalyst (dibutyl tin dilaurate) and stir evenly, then add them to the base rubber and evacuate to a vacuum degree of 0.05 MPa, and stir for 25 minutes.
[0027] (4) Finally, coupling agents KH550 and KH792 were added to the base glue in a mass ratio of 3:1. The mixture was evacuated to a vacuum degree of 0.05 MPa and a temperature of 40°C. The mixture was stirred for 35 minutes to obtain a single-component, low water permeability, fast-curing sealant.
[0028] Example 2 The difference from Example 1 is that 9 parts of butyl rubber and 2.5 parts of polyisobutylene are added.
[0029] Example 3 The difference from Example 1 is that butyl rubber is added in an amount of 5 parts and polyisobutylene is added in an amount of 2 parts.
[0030] Example 4 The difference from Example 1 is that tetrabutyl ketone oxime silane is replaced by phenyl tributyketone oxime siloxane.
[0031] Example 5 Different from Example 1, tetrabutyl ketone oxime silane is replaced by a mixture of phenyltributyketone oxime siloxane and tetrabutyl ketone oxime siloxane, with a mass ratio of 1:2.
[0032] Comparative Example 1 The difference from Example 1 is that no butyl rubber and polyisobutylene are added.
[0033] Comparative Example 2 Different from Example 1, no polyisobutylene was added.
[0034] Comparative Example 3 The difference from Example 1 is that no butyl rubber is added.
[0035] Comparative Example 4 The difference from Example 1 is that no catalyst is added in step (3), and in step (4), the coupling agent and the catalyst are mixed and then added to the base rubber.
[0036] Comparative Example 5 Commercially available Huitian photovoltaic module sealant HT906Z.
[0037] The sealants obtained in the above examples and comparative examples were tested according to the national standard GB / T29595-2013. The test results are shown in Table 1.
[0038] Table 1 Performance test results of examples and comparative examples
[0039] From the data of Example 1 and Comparative Examples 1 to 3 in the table, it can be seen that by introducing butyl rubber and polyisobutylene into the silicone rubber system, the water vapor permeability of the photovoltaic adhesive can be significantly reduced. From Example 1 and Comparative Example 4, it can be seen that by adding the catalyst in advance, the curing of the present invention is significantly improved compared with the conventional method of adding the catalyst later.
Claims
1. A single-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed, characterized in that: The invention comprises the following raw materials in parts by weight: 50-150 parts of α,ω-dihydroxy polydimethylsiloxane; Butyl rubber 5-20 parts; Polyisobutylene 2-10 parts; 100-200 parts of modified nano calcium carbonate; 1-10 parts of cross-linking agent; Coupling agent 0.5-5 parts; Catalyst 0.01-0.1 parts.
2. The one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 100-150 parts of α,ω-dihydroxy polydimethylsiloxane; Butyl rubber 10-20 parts; Polyisobutylene 5-10 parts; 150-200 parts of modified nano calcium carbonate; 5-10 parts of cross-linking agent; Coupling agent 0.5-2 parts; Catalyst 0.01-0.05 parts.
3. The one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 1, characterized in that: The structural formula of the α,ω-dihydroxy polydimethylsiloxane is HO-[(CH3)2SiO] m -H, wherein m is 50-1000; the kinematic viscosity of α,ω-dihydroxy polydimethylsiloxane at 25°C is preferably 10000-80000cp, further preferably 20000-80000cp, and more preferably 20000cp; The butyl rubber has a kinematic viscosity of 5000-800000 cp at 25° C., preferably 50000-800000 cp, and more preferably 100000 cp-500000 cp; The polyisobutylene has a kinematic viscosity at 25° C. of 100,000 to 800,000 cp, preferably 200,000 to 800,000 cp, and more preferably 500,000 to 800,000 cp.
4. The one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 1, characterized in that: The modified nano calcium carbonate is prepared from calcium carbonate emulsion and modified by stearic acid; the water content of the modified nano calcium carbonate is 0.1-0.5% and the specific surface area is 15-40m 2 / g, oil absorption value is 25~35m 2 / g, whiteness of 93-97, particle size and shape of prism or cube; preferably, moisture content of 0.1-0.3%, specific surface area of 25-40m 2 / g, oil absorption value is 30-35m 2 / g, whiteness is 93-97, and particle size is prismatic.
5. The one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 1, characterized in that: The coupling agent is one or more of a monoaminosilane coupling agent, a bisaminosilane coupling agent, an epoxysiloxane or an oligomer amino coupling agent; preferably, the coupling agent is a monoaminosilane coupling agent and a bisaminosilane coupling agent compounded in a mass ratio of 3:
1.
6. The one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 1, characterized in that: The crosslinking agent is one or more of phenyltributylon oxime siloxane, tetrabutyl oxime siloxane, methyltributylon oxime siloxane or vinyltributylon oxime siloxane, preferably at least one of phenyltributylon oxime siloxane or tetrabutyl oxime siloxane.
7. The one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 1, characterized in that: The catalyst is at least one of dibutyltin diacetate, dibutyltin dilaurate, chelated tin, stannous octoate or stannous isooctanoate.
8. A method for preparing a one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (1) heating and kneading α,ω-dihydroxypolydimethylsiloxane, butyl rubber and polyisobutylene; (2) Add modified nano calcium carbonate, heat and knead; (3) After cooling, add the cross-linking agent and catalyst and stir; (4) Add a coupling agent and stir to obtain a single-component, low water permeability, fast-curing sealant.
9. The method for preparing a one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed according to claim 8, characterized in that: The kneading temperature in step (1) is 100-160°C, preferably 120-150°C, and more preferably 140-150°C; the kneading time in step (1) is 10-60 min, preferably 15-45 min, and more preferably 25-35 min; the kneading temperature in step (2) is 90-140°C, preferably 110-140°C, and more preferably 130-140°C; the kneading time in step (2) is 2-8 h, preferably 2-5 h, and more preferably 3~4h; after step (3) is cooled to 40~50°C, a cross-linking agent and a catalyst are added; the stirring temperature of step (3) and step (4) is 30~80°C, preferably 30~60°C, and more preferably 40~50°C; the stirring time of step (3) is 10~60min, preferably 20~50min, and more preferably 25~35min; the stirring time of step (4) is 10~60min, preferably 25~45min, and more preferably 30~40min.
10. Application of a one-component photovoltaic adhesive with low water vapor transmission rate and fast curing speed, characterized in that: Sealant for offshore photovoltaic or heterojunction photovoltaic products.
Citation Information
Patent Citations
Butyl rubber for edge sealing of N-type battery and preparation method of butyl rubber
CN117683488A